The different risk factors for isolated diastolic hypertension and isolated systolic hypertension: a national survey - Kun Xie; Xiufang Gao; Liwen Bao; Ying Shan; Haiming Shi; Yong Li (BMC, 2021)
Abstract Background Hypertension is highly prevalent and is one of the modifiable risk factors for cardiovascular outcomes. Isolated diastolic hypertension (IDH), however, tends to be ignored due to insufficient recognition. We sought to depict the clinical manifestation of IDH and isolated systolic hypertension (ISH) to find a more efficient way to improve the management. Methods Patients with primary hypertension aged over 18 years were investigated from all over the country using convenience sampling during 2017-2019. IDH was defined as systolic blood pressure (SBP) < 140 mmHg and diastolic blood pressure (DBP) ≥90 mmHg. ISH was defined as SBP ≥ 140 mmHg and DBP < 90 mmHg. Results A total of 8548 patients were screened, and 8475 participants were included. The average age was 63.67 ± 12.78 years, and males accounted for 54.4%. Among them, 361 (4.3%) had IDH, and 2096 had ISH (24.7%). Patients with IDH (54.84 ± 13.21 years) were much younger. Aging turned out to be negatively associated with IDH but positively associated with ISH. Multivariate logistic regression analysis showed BMI was a significant risk factor for IDH (OR 1.30, 95%CI 1.05-1.61, p = 0.018), but not for ISH (OR 1.05, 95%CI 0.95-1.16, p = 0.358). Moreover, smoking was significantly associated with IDH (OR 1.36, 95%CI 1.04-1.78, p = 0.026) but not with ISH (OR 1.04, 95%CI 0.90-1.21, p = 0.653). Conclusions Patients with IDH were much younger, and the prevalence decreased with aging. BMI and smoking were remarkably associated with IDH rather than ISH. Keeping fit and giving up smoking might be particularly efficient in the management of young patients with IDH. Trial registration NCT03862183 , retrospectively registered on March 5, 2019.